PUBLIC POLICY INNOVATION TO ENHANCE THE COMPETITIVENESS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN KEPAHIANG REGENCY, BENGKULU PROVINCE - Zetia Wijayanti; Pandu Pamungkas (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to analyze public policy innovations carried out by the Kepahiang Regency Government in an effort to increase the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. The method used is the Literature Review Research Method from various sources related to Public Policy Innovation such as previous research, government reports and Mass Media. The results of the study indicate that the Kepahiang Regency Government has initiated various innovative policies such as digitalization of local product marketing, digital literacy training for MSMEs, and strengthening the collaborative ecosystem between the government, private sector, and communities. However, challenges still exist in the limitations of digital infrastructure, low technological literacy, and suboptimal coordination between agencies. By strengthening aspects of technology-based policy innovation and community participation, the competitiveness of MSMEs in Kepahiang Regency has the potential to increase significantly.